Uso de serviços públicos de saúde bucal pela população adulta - Rafaela da Silveira Pinto (2015)
Explain the factors associated with use of dental services factors can provide knowledge to understand the reasons that lead individuals to seek for health care and the formulation of public policies most appropriate to reality. This study used a sample of adults listed in the database of the population of Minas Gerais oral health survey. It was an epidemiological study, representative for the state of Minas Gerais, that investigated the main oral health disorders and socioeconomic aspects. The aim of this study was known the prevalence and associated factors with the use of public services by adults of Minas Gerais. The dependent variable was the type of service used, categorized in public and private. The independent variables were selected and grouped for inclusion in the model according to an adaptation of the behavioral model of Andersen and Davidson. For the data analysis in the first paper, a hierarchical model was used. For each block of variables in hierarchical levels, were estimated by logistic regression unadjusted and adjusted odds ratios and confidence intervals at 95% . The Complex Samples module of SPSS 19.0 was used, considering the sampling design. It was found that the factors that were associated with the use of public services by adults in the final model are being of black race / skin color, belong to families with more than 4 residents and lower income, living in smaller towns and have more teeth requiring treatment. In the second study, it was used STATA 12.0 program. The variables that represent the life context of the individuals were inserted and the multilevel model was used for the analysis. The neighborhood level variables were from the Population Census of the year 2010 and the variables at the municipal level were from available public databases relating to oral health services. Also at the municipal level the MHDI variable was chosen to represent quality of life in the cities of the survey. In relation to individual variables, we used those that remained significant in the article cited above. In the final model, in relation to individual variables, the following were associated with greater use of public dental services: lower family income, greater number of residents in the household and more teeth needing treatment. With regard to context variables, the worst infrastructure leads to less use of public services. Thus it is concluded that the use of public services is linked to family income, the way this income is divided in households, the need for treatment presented by the individual and the organization of the infrastructure of existing oral health services in the municipality. The Unified Health System of Brazil has played his role to be present to those who need it most. Health differences need to be addressed through intersectoral public policies that allow the modification of social determinants.